The Effect of Aerosols on Fog Lifetime: Observational Evidence and Model Simulations. Issue 2 (25th January 2021) - Yan, Shuqi; Zhu, Bin; Zhu, Tong; Shi, Chune; Liu, Duanyang; Kang, Hanqing; Lu, Wen; Lu, Chunsong
Abstract: The aerosol–cloud interaction (ACI) and aerosol–radiation interaction (ARI) have notable influences on clouds, but their effects on fog are rarely analyzed before. Previous studies indicate that fog frequency in East China has been decreasing, and we further reveal that fog duration increases during 1960–2010. We hypothesize that this trend is related to the increase of aerosol pollution and perform WRF‐Chem simulations to study the ARI and ACI effects. Results show that ACI significantly advances fog formation, delays fog dissipation, and increases fog duration by about 1 h in a case study, while ARI has negligible effect. The more but smaller fog droplets produced in polluted conditions significantly inhibit droplet sedimentation and reduce solar radiation, therefore provide favorable conditions for the duration of fog. Under extremely polluted conditions, ACI effect also far overweighs ARI effect. To shorten the duration of dense fog, our findings suggest the necessity for mitigating emissions. Plain Language Summary: Aerosols, the suspensions of solid or liquid particles in the air, affect clouds through aerosol–cloud interaction (ACI) and aerosol–radiation interaction (ARI). The ARI refers to that aerosols affect the meteorological conditions in clouds by scattering and absorbing radiation. The ACI refers to that clouds form on aerosols if aerosols absorb sufficient water vapor. Fog is a kind of near‐surface cloud. The ARI and ACI could have both notable influences on fog, but their effects are rarely analyzed before. Previous studies indicate that fog frequency in East China has been decreasing, and in this study we further reveal that fog duration increases during 1960–2010. We hypothesize that this trend is related to the increase of aerosol pollution and perform numerical simulations to study the ARI and ACI effects. Results show that ACI significantly advances fog formation, delays fog dissipation, and increases fog duration by about 1 h in the case study, while ARI has negligible effect. The ACI can significantly inhibit fog droplet sedimentation and reduce solar radiation, therefore provide favorable conditions for the duration of fog. Our findings suggest that reducing emissions could shorten fog duration and mitigate the hazards of fog. Key Points: Fog frequency in East China is decreasing, and fog duration is increasing The increase in fog duration is mainly caused by aerosols Aerosol–cloud interaction plays a more important role in increasing fog duration than aerosol–radiation interaction